International Institutions Activity in the Field of Food Security - A. A. Pryanikova (Управленческое консультирование)
Globalization processes have had a significant impact on agricultural and food systems around the world, resulting in a strong correlation between international political and economic events and food security. The dependence of actors on each other, the transcendental nature of food problems makes them even more difficult to eliminate. The category of food security itself reflects not only the food supply of individual households or regions, but also demonstrates the level of scientific and technological progress, socio-economic development, and the success of monitoring the natural and climatic situation in the state as a whole. This article examines the main international organizations involved in solving the problem of food security, as well as mechanisms aimed at eliminating it.The aim of the article is to assess the effectiveness of international organizations in the field of food security. The scientific novelty of the article consists in the attempt not only to describe the activities of major international institutions in the field of food security, but also to assess the effectiveness of these activities against the background of the above-mentioned factors. In the scientific literature, such studies dating from 2022–2023 have not yet been presented.The key research method was document analysis.The empirical basis was statistic data, the speeches and statements of Russian and foreign politicians and experts in the field of food. The author identifies the key areas of activity of these organizations in the field of food independently of each other, as well as in interaction, and offers their assessment of their effectiveness. The article offers a conclusion about the role of the food problem for the world community at the present time and about the level of involvement of international organizations in eliminating this problem. As a result, some new ways of international cooperation in this area are proposed.